Immunoprophylactic Control Strategy for Tropical Fasciolosis: A Possibility - Niranjan Kumar; Prem Sagar Maurya; Jayesh B Solanki; Anil Kumar Mishra (Journal of Vaccines and Immunology - Peertechz Publications, 2016)
Fasciolosis is a wide spread economically important helminthosis caused by Fasciola  epatica and F. gigantica and considered as a limiting factor for domestic livestock production. The strategic control measures against fasciolosis mainly depend upon judicious use of the anti-fl uke drugs. Repeated applications and need for skilled labour make chemotherapy for fasciolosis a more costly affair. Chemotherapy has certain limitations on account of development of resistance to anthelmintics. Since the cost of treatment impedes application of chemotherapy within the rural areas of developing countries, other control measures such as development of vaccines are therefore, warranted. Attempts made to confer acquired resistance in ruminants against the disease, using viable attenuated metacercariae, crude somatic antigens excretory/secretary products, native, recombinant and peptide antigens with different adjuvant formulations and / or passive transfer of immunity through serum / immune cells of infected host have been partly successful.